A new path in defining light parameters for hair growth: discovery and modulation of photoreceptors in human hair follicle - Buscone, Serena; Sticht, Carsten; Gretz, Norbert (Lasers in surgery and medicine, 2017)
Background and Objective Though devices for hair growth based on low levels of light have shown encouraging results, further improvements of their efficacy is impeded by a lack of knowledge on the exact molecular targets that mediate physiological response in skin and hair follicle. The aim of this study was to investigate the expression of selected light-sensitive receptors in the human hair follicle and to study the impact of UV-free blue light on hair growth ex vivo. Material and Methods The expression of Opsin receptors in human skin and hair follicles has been characterized using RT-qPCR and immunofluorescence approaches. The functional significance of Opsin 3 was assessed by silencing its expression in the hair follicle cells followed by a transcriptomic profiling. Proprietary LED-based devices emitting two discrete visible wavelengths were used to access the effects of selected optical parameters on hair growth ex vivo and outer root sheath cells in vitro. Results The expression of OPN2 (Rhodopsin) and OPN3 (Panopsin, Encephalopsin) was detected in the distinct compartments of skin and anagen hair follicle. Treatment with 3.2 J/cm2 of blue light with 453 nm central wavelength significantly prolonged anagen phase in hair follicles ex vivo that was correlated with sustained proliferation in the light-treated samples. In contrast, hair follicle treatment with 3.2 J/cm2 of 689 nm light (red light) did not significantly affect hair growth ex vivo. Silencing of OPN3 in the hair follicle outer root sheath cells resulted in the altered expression of genes involved in the control of proliferation and apoptosis, and abrogated stimulatory effects of blue light (3.2 J/cm2; 453 nm) on proliferation in the outer root sheath cells. Conclusions We provide the first evidence that (i) OPN2 and OPN3 are expressed in human hair follicle, and (ii) A 453 nm blue light at low radiant exposure exerts a positive effect on hair growth ex vivo, potentially via interaction with OPN3. Lasers Surg. Med. 49:705-718, 2017. © 2017 Wiley Periodicals, Inc.